2021
DOI: 10.3390/cryst11020169
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Detection Based on 2D Bi2Se3/ZnO Nanowire Heterojunction

Abstract: The investigation of photodetectors with broadband response and high responsivity is essential. Zinc Oxide (ZnO) nanowire has the potential of application in photodetectors, owing to the great optoelectrical property and good stability in the atmosphere. However, due to a large number of nonradiative centers at interface and the capture of surface state electrons, the photocurrent of ZnO based photodetectors is still low. In this work, 2D Bi2Se3/ZnO NWAs heterojunction with type-I band alignment is established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The metal–semiconductor–metal (MSM) deep-UVPDs were fabricated using the standard semiconductor fabrication techniques, which is a photolithography process employed to pattern the symmetric metal electrode pairs [ 34 , 35 , 36 ]. The diagrammatic structure of the PEC UVPD is shown in Figure 1 a.…”
Section: Methodsmentioning
confidence: 99%
“…The metal–semiconductor–metal (MSM) deep-UVPDs were fabricated using the standard semiconductor fabrication techniques, which is a photolithography process employed to pattern the symmetric metal electrode pairs [ 34 , 35 , 36 ]. The diagrammatic structure of the PEC UVPD is shown in Figure 1 a.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they produced different composite materials and application fields by adjusting the sizes of and the growth methods for both the GQDs and the ZnO nanowires (nanorods). At present, the composites based on ZnO nanowires still have good development and broad application prospects [36]. Dhar et al [37] deposited GQDs with a size of approximately 6 nm on the surfaces of ZnO nanorods with a diameter of 100 nm for ultraviolet (UV) light detection in 2016.…”
Section: Zno-0d Graphene Quantum Dot Compositementioning
confidence: 99%
“…Various strategies have been implemented to fabricate photodetectors exhibiting high-efficiency, broadband photodetection performance. Zeng et al built a photodetector based on a two-dimensional Bi 2 Se 3 /ZnO NWA heterojunction possessing a high photoresponsivity (0.15 A W –1 ) at 377 nm . Long et al reported an interesting SnO 2 –NiO PN junction-based photodetector with a cross-bar structure, showing a remarkable responsivity and detectivity of 30.29 mA W –1 and 2.24 × 10 11 Jones at 0 V bias, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al built a photodetector based on a two-dimensional Bi 2 Se 3 /ZnO NWA heterojunction possessing a high photoresponsivity (0.15 A W −1 ) at 377 nm. 30 Long et al reported an interesting SnO 2 − NiO PN junction-based photodetector with a cross-bar structure, 31 showing a remarkable responsivity and detectivity of 30.29 mA W −1 and 2.24 × 10 11 Jones at 0 V bias, respectively. However, the properties of these materials are still insufficient for the photoresponsivity or detectivity of these materials was not satisfactory for broadband photodetectors.…”
Section: Introductionmentioning
confidence: 99%